Tritrophic associations and identification key for European species of the genus Binodoxys (Mackauer) (Hymenoptera: Braconidae: Aphidiinae) - Lazarević Maja J.; Žikić Vladimir A.; Milenković Darija N.; Tomanović Željko M. (Archives of Biological Sciences)
The genus Binodoxys includes only nine species found in Europe, yet despite its frequent occurrence, it remains insufficiently studied. This study addresses this knowledge gap through an exhaustive literature review and material collection, and a compilation of a comprehensive list detailing tritrophic associations. Based on the available molecular data, we constructed a maximum likelihood tree for six European species. Several new hosts were identified for the first time, and the geographical distribution of one species was broadened. An identification key for females of European Binodoxys species is provided. Future studies should prioritize gathering host data and investigate the existence of cryptic species among polyphagous species. Furthermore, the status of the three species not analyzed in this study due to the lack of material should be investigated by encompassing both morphological and molecular approaches.